Words and Images. - The PhotoGallery, Ottawa (Ottawa : The National Film Board of Canada, 1980)
April, Raymonde ; Astman, Barbara ; Condé, Carole ; Beveridge, Karl ; Corman, don ; General Idea ; Raskin, Lawrie ; Robideau ; Semak, Michael ; Smylski, Peter T.
Words and Images / Mots et Images, The PhotoGallery, Ottawa, June 27 to September 1, 1980
boek